Mechanism of Huaiqihuang (HQH) against cyclophosphamide (CYP)-induced hippocampal neurotoxicity based on network pharmacology, molecular docking and experimental verification - Zhang, Yueming; Huang, Fengwei; Zhai, Jinghui; Sun, Jingmeng; Li, Boyu; Zhang, Sixi (Frontiers in Cell and Developmental Biology, 2025)
BackgroundCyclophosphamide (CYP) is widely used for the treatment of cancer and autoimmune diseases. However, neurotoxicity accompanied with application of CYP seriously affects the final clinical outcome. Huaiqihuang (HQH) is a Chinese herbal complex with immunomodulatory effect and widely used for treating various diseases. The present research was conducted to evaluate the protective effect of HQH against CYP-induced neurotoxicity and to elucidate the underlying mechanisms.MethodsSprague–Dawley rats were randomly divided into four groups (10 per group): the CYP-only group (single dose of 200 mg/kg), low- and high-dose HQH + CYP groups (pretreatment with 3 or 6 g/kg HQH for 5 days), and control (saline) group. Histopathological analysis and behavioral tests was used to evaluate the therapeutic effects of HQH on CYP-induced neurotoxicity. Network pharmacology, molecular docking, and Western blot were employed to assess the anti-neurotoxicity mechanisms.ResultsBoth doses of HQH restored histopathological aberrations, oxidative stress and inflammation caused by CYP in rats. Behavioral tests showed that HQH pretreatment improved motor coordination and balance in CYP-treated rats. Network pharmacology identified core targets including HSP90AA1, TP53, MAPK1, AKT1, RELA, TNF. Molecular docking revealed that TNF, HSP90AA1, TP53, and MAPK1 had strong binding affinities with CYP. Experimental validation using Western blot confirmed that HQH significantly decreased the protein expression of TNF, HSP90AA1, TP53, and MAPK1 in hippocampal tissues.ConclusionHQH mitigates CYP-induced hippocampal neurotoxicity by decreasing oxidative stress, and inflammation, with HSP90AA1 being a key target, providing a novel therapeutic strategy for chemotherapy-associated cognitive impairment.